2019
DOI: 10.1080/21645515.2019.1596713
|View full text |Cite
|
Sign up to set email alerts
|

Low awareness of influenza vaccination among pregnant women and their obstetricians: a population-based survey in Beijing, China

Abstract: We assessed how an awareness of influenza vaccination might influence both the willingness of pregnant women to be vaccinated and the readiness of obstetricians to recommend antenatal influenza vaccination in Beijing, China. From March to April 2016, we surveyed pregnant women who were attending antenatal clinics at eight hospitals in Beijing, along with obstetricians at the same clinics. Demographic, attitudinal, and behavioral information regarding influenza vaccination were collected using structured questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 39 publications
0
25
0
2
Order By: Relevance
“…A recent population-based survey in China has reported only 11% of pregnant women reported being willing to receive an influenza while pregnant. 34 The same survey also indicated that only 20% of the obstetricians being willing to recommend influenza vaccination to their pregnant women. Other study has shown a systematic different in socio-demographic and health characteristics of those who decided to get vaccinated with an influenza vaccine.…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent population-based survey in China has reported only 11% of pregnant women reported being willing to receive an influenza while pregnant. 34 The same survey also indicated that only 20% of the obstetricians being willing to recommend influenza vaccination to their pregnant women. Other study has shown a systematic different in socio-demographic and health characteristics of those who decided to get vaccinated with an influenza vaccine.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…In other words, a higher proportion of unvaccinated women believed that they were at risk of influenza infection or exposure compared with those who then unvaccinated, but later got the vaccine, which seems illogical. This might be explained that when translated into Thai language, the "influenza Age, median (IQR) 29 (28)(29)(30)(31)(32) 31 (29)(30)(31)(32)(33)(34)(35)(36)(37)(38) .20…”
Section: Con Clus Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In uenza vaccination of pregnant women not only effectively prevents maternal in uenza during the in uenza season, but also produces protective antibodies that can pass through the placental barrier; and thus effectively prevents infection in infants under 6 months of age who are not suitable for in uenza vaccination [14][15] . In developed countries such as the United States, the in uenza vaccination rate for pregnant women has approached or exceeded 50% [16][17] , while the in uenza vaccination rate of pregnant women in China has been very low [18] . The latest guidelines suggest [19] that pregnant women be vaccinated at any stage of pregnancy, and that the prevention of contracting in uenza by infants under 6 months of age occur through the vaccination of their mothers during pregnancy, and also of their family members and caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Influenza vaccination of pregnant women not only effectively prevents maternal influenza during the influenza season, but also produces protective antibodies that can pass through the placental barrier; and thus effectively prevents infection in infants under 6 months of age who are not suitable for influenza vaccination [14][15] . In developed countries such as the United States, the influenza vaccination rate for pregnant women has approached or exceeded 50% [16][17] , while the influenza vaccination rate of pregnant women in China has been very low [18] . The latest guidelines suggest [19] that pregnant women be vaccinated at any stage of pregnancy, and that the prevention of contracting influenza by infants under 6 months of age occur through the vaccination of their mothers during pregnancy, and also of their family members and caregivers.…”
Section: Discussionmentioning
confidence: 99%